Pengaruh Perceived Organizational Support terhadap Organizational Citizenship Behavior dengan Affective Commitment sebagai Variabel Mediasi pada Karyawan PT Sapta Sentosa Jaya Abadi Mukomuko - Selfita Liasari; Chichi Andriani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the effect of perceived organizational support (POS) on organizational citizenship behavior (OCB) considering the mediating role of affective commitment. A quantitative approach with a causal research design was employed, and data analysis was conducted using Structural Equation Modeling–Partial Least Square (SEM-PLS) through SmartPLS 4 software. The population of this study consisted of all employees at PT Sapta Sentosa Jaya Abadi Mukomuko, totaling 90 respondents selected using a saturated sampling technique. The results indicate that affective commitment mediates the relationship between POS and OCB. POS has a significant influence on both OCB and affective commitment. These findings specifically highlight that POS plays a crucial role in fostering OCB among employees. The study is grounded in Social Exchange Theory, which emphasizes that when employees perceive strong organizational support, it enhances their emotional attachment and motivates voluntary behaviors beyond formal job responsibilities. This underscores the vital role of organizations in creating a work environment where employees feel valued and supported, both in terms of assistance and overall well-being.